Getting it right American military reforms after Vietnam to the Persian Gulf and beyond - Dunnigan, James F. (W. Morrow and Co., 1993)
In February 1991 U.S. troops won the first battle of a war and did so with minimal losses. Remarkably, this had never happened before. Getting It Right is an insider's look at how this occurred. It covers subjects as wide-ranging and essential to the understanding of U.S. military affairs as the nation's historically based unpreparedness for war - lessons that were repeatedly learned and forgotten from war to war-the introduction of nuclear weapons to post-World War II military policy, the Cold War fear of the Soviet Union, and the military before, during, and after Vietnam. Most important, however, it stresses the immeasurable gains made in the armed forces during the last two decades, gains that led to successes in the Gulf War and improved chances for continued success in the future. Contrary to popular belief, this reversal has less to do with high-tech weapons than with better training for officers and troops. Haunted by the specter of the Vietnam War, officers have embraced a more pragmatic and professional attitude; troops are more carefully selected and better paid; training has become more sophisticated with the use of wargaming, computer simulations, and more intensive field practice. Using the Army as a touchstone, but including all branches of the armed services, Getting It Right also discusses how the military is dealing with the issues of racism, sexism, and homosexuality and with the cost of keeping troops combat-ready. It additionally looks at how much our military is costing and where cuts can and cannot be made as it heads toward the end of the American Century. Getting It Right is a strong and insightful look at what a strong and efficient military can mean in times of war, and peace.